serum level of IgA, IgG, IgM, CA125, CEA, migration inhibitory factor-related protein 14 (MRP14), stromal cell-derived factor 1 (SDF-1), fibroblast-specific protein 1 (FSP-1), and C-X-C Motif Chemokine Receptor 4 (CXCR4) in gastric cancer after treatment : serum markers in gastric cancer - Huang, Ying; Hu, Yueming; Gu, Fengwei; Ni, Yufeng (Journal of Medical Biochemistry, 2025)
Objective: The current study was undertaken to assess the effects of the treatment on ( IgA, IgG, IgM, CA125, CEA, migration inhibitory factor-related protein 14 (MRP14), stromal cell-derived factor 1 (SDF-1), fibroblast-specific protein 1 (FSP-1), and C-X-C Motif Chemokine Receptor 4 (CXCR4) in patients with advanced gastric cancer.Methods: In this randomized clinical trial, 100 patients with gastric cancer were recruited after excluding 8 ineligible cases and assigned to receive either oxaliplatin (reference group) or the SOX regimen (observation group) via random number table method at a ratio of 1:1, with 50 patients in each group. The primary clinical endpoint was clinical efficacy, and secondary endpoints included immune function, tumor markers, and chemotherapy toxicities.Results: The SOX regimen was associated with significantly higher clinical efficacy versus oxaliplatin monotherapy, as indicated by the higher disease control rate and objective remission rate (P
Keywords: ( IgA, IgG, IgM, CD3 , CD4 and NK cells and CD8 , CA125, CEA, migration inhibitory factor-related protein 14 (MRP14), stromal cell-derived factor 1 (SDF-1), fibroblast-specific protein 1 (FSP-1), and C-X-C Motif Chemokine Receptor 4 (CXCR4)